Interaction of Trivalent An(III) with Glenium 51: the effect of ionic strength - Özyagan, Sema; Sittel, Thomas; Skerencak-Frech, Andrej; Panak, Petra (Inorganic chemistry, 2025)
In this work, we present novel insights on the complexation of Cm(III) with the polycarboxylate ether-based concrete superplasticizer Glenium® 51 as a function of ionic strength (Im(NaCl) = 0.10-3.49 mol kg-1) and pHm. By using the metal ion charge neutralization model, conditional stability constants are derived from spectral analysis (time-resolved laser fluorescence spectroscopy, TRLFS). Increasing the pHm results in the formation of distinct Cm(III) complex species: CmGle, Cm(OH)Gle, and Cm(OH)2Gle. With increasing ionic strength, the CmGle and Cm(OH)Gle formation is less favored, resulting in a decrease of the complex stability by 1.2 and 0.5 orders of magnitude, respectively. In contrast, the formation of the third complex species Cm(OH)2Gle is favored, leading to an overall increase of the stability constant by 1.1 orders of magnitude. With the specific ion interaction theory (SIT), the conditional stability constants are extrapolated to zero ionic strength, yielding logβ10 (CmGle) = 7.46 ± 1.1, logβ20 (Cm(OH)Gle) = 14.2 ± 1.4 , and logβ30 (Cm(OH)2Gle) = 18.0 ± 1.8. These novel studies are essential for modeling actinide behavior with concrete additives in the near-field of a nuclear waste repository in the clay rock formations of Northern Germany, where increased ionic strengths are ubiquitous.
Online veröffentlicht: 29. Oktober 2025
Gesehen am 03.12.2025